The Effect of Maltodextrin Concentration and Drying Temperature on the Instant Coffee Production with Spray Drying Method - Hariyadi, Tri (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
The operating temperature and the addition of fillers such as maltodextrin had a valuable effect on the quality of instant coffee production. Based on this, the purpose of this research is to determine the effect of maltodextrin concentration and operating temperature on the quality of instant coffee powder produced by the spray drying method. The variation of operating temperature was conducted in the range of 120 to 170⁰C without the addition of maltodextrin, and the variation of maltodextrin concentration was conducted in the range of 5% to 35% (w/v) with the optimum operating temperature at the lowest water content. The observed quality parameters of the coffee were yield, moisture, ash, caffeine content, and organoleptic tests. The optimum operating temperature was 140⁰C with a moisture content of 5.17% (w/w). The best instant coffee quality was achieved with a 15% concentration of maltodextrin, with a yield of 50.49%, a moisture content of 3.94% (w/w), an ash content of 6.66% (w/w), and a caffeine content of 5.16% (w/w). Based on the organoleptic test, the coffee sample with 15% maltodextrin had a brownish color, a moderately strong aroma, was moderately bitter, and was liked by the panelists.